Sport motivation in high-performance basketball female players of national teams from Argentina, Chile, Colombia, Ecuador, Paraguay, Perú y Venezuela - Muñoz, Liliana; Morillo Puente, Solbey; Hernández Bohórquez, Edwin Eduardo (Pensando Psicología, 2021)
Aim: To analyze levels of extrinsic, intrinsic, and non-motivation in 83 women between 18 and 23 years of age who belong to seven basketball national teams of seven Latin American countries.Methodology:From the data collection, an observational, cross-sectional, and correlational research was carried out, in which the Sport Motivation Scale (Pelletier et al., 1995) was applied. The most representative results show that 82.7 % and 43.4 % of participants presented high levels of motivation, intrinsic and extrinsic respectively.Results: Levels of intrinsic motivation differ according to the countries, but not in a statistically significant way, while the extrinsic motivation did vary significantly between countries.Conclusions: It was identified that 13.4 % of non-motivation is present in the players and that there are no significant differences between countries.
Keywords: Latin America; sport; statistics; play